Defective 2D Covalent Organic Frameworks for Postfunctionalization - Li, Zhen; Liu, Zhi‐Wei; Li, Zeyu; Wang, Tian‐Xiong; Zhao, Fulai; Ding, Xuesong; Feng, Wei; Han, Bao‐Hang (Advanced functional materials, 2020)
Defects are deliberately introduced into covalent organic frameworks (COFs) via a three‐component condensation strategy. The defective COFs (dCOF‐NH2‐Xs, X = 20, 40, and 60) possess favorable crystallinity and porosity, as well as have active amine functional groups as anchoring sites for further postfunctionalization. By introducing imidazolium functional groups onto the pore walls of COFs via the Schiff‐base reaction, dCOF‐ImBr‐Xs‐ and dCOF‐ImTFSI‐Xs‐based materials are employed as all‐solid‐state electrolytes for lithium‐ion conduction with a wide range of working temperatures (from 303 to 423 K), and the ion conductivity of dCOF‐ImTFSI‐60‐based electrolyte reaches 7.05 × 10−3 S cm−1 at 423 K. As far as it is known, it is the highest value for all polymeric crystalline porous material based all‐solid‐state electrolytes. Furthermore, Li/dCOF‐ImTFSI‐60@Li/LiFePO4 all‐solid Li‐ion battery displays satisfactory battery performance under 353 K. This work not only provides a new methodology to construct COFs with precisely controlled defects for postfunctionalization, but also makes them promising candidate materials as all‐solid‐state electrolytes for lithium‐ion batteries operate at high temperatures. Defective COFs (dCOFs) with active amine functional groups as anchoring sites for postfunctionalization are constructed. After the postfunctionalization process, dCOF‐ImBr‐Xs‐ and dCOF‐ImTFSI‐Xs‐based materials are employed as all‐solid‐state electrolytes for lithium‐ion conduction. As a result, the dCOF‐ImTFSI‐60@Li‐based electrolyte exhibits outstanding lithium‐ion conductivity values, and the Li/dCOF‐ImTFSI‐60@Li/LiFePO4 all‐solid Li‐ion battery displays satisfactory battery performance under 353 K.